Homo naledi cranial remains from the Lesedi chamber of the rising star cave system, South Africa. Issue 132 (July 2019) - de Ruiter, Darryl J.; Laird, Myra F.; Elliott, Marina; Schmid, Peter; Brophy, Juliet; Hawks, John; Berger, Lee R.
Abstract: Excavations in the Lesedi Chamber (U.W. 102) of the Rising Star cave system from 2013 to 2015 resulted in the recovery of 131 fossils representing at least three individuals attributed to Homo naledi . Hominin fossils were recovered from three collection areas within the Lesedi Chamber. A partial skull with near complete dentition (LES1) and an associated partial skeleton were recovered from Area 102a, while craniodental remains from two other individuals were recovered from Areas 102b and 102c. Here we present detailed anatomical descriptions and metrical comparisons of the Lesedi Chamber H. naledi craniodental remains that preserve diagnostic morphology. The LES1 skull is a presumed male that is slightly larger in size, and shows greater development of ectocranial structures compared to other H. naledi specimens from the Dinaledi Chamber of the Rising Star cave system. Otherwise the Lesedi fossils are notably similar to the Dinaledi fossils in shape and morphology. The Lesedi fossils also preserve the delicate nasal and lacrimal bones that are otherwise unrecorded in the Dinaledi sample. Limited morphological differences between the Dinaledi and Lesedi Chamber hominin samples provides support for the hypothesis that these two assemblages share a close phyletic relationship.